Spectroscopic Characterization of Aqueous and Colloidal Am(III)-CO3 Complexes for Monitoring Species Evolution - Kim, Hee-Kyung (Journal of nuclear fuel cycle and waste technology (Online), 2022)
Carbonates are inorganic ligands that are abundant in natural groundwater. They strongly influence radionuclide mobility by forming strong complexes, thereby increasing solubility and reducing soil absorption rates. We characterized the spectroscopic properties of Am(III)-carbonate species using UV-Vis absorption and time-resolved laser-induced fluorescence spectroscopy. The deconvoluted absorption spectra of aqueous Am(CO3)2 − and Am(CO3)3 3− species were identified at redshifted positions with lower molar absorption coefficients compared to the absorption spectrum of aqua Am3+. The luminescence spectrum of Am(CO3)3 3− was red-shifted from 688 nm for Am3+ to 695 nm with enhanced intensity and an extended lifetime. Colloidal Am(III)-carbonate compounds exhibited absorption at approximately 506 nm but had non-luminescent properties. Slow formation of colloidal particles was monitored based on the absorption spectral changes over the sample aging time. The experimental results showed that the solubility of Am(III) in carbonate solutions was higher than the predicted values from the thermodynamic constants in OECD-NEA reviews. These results emphasize the importance of kinetic parameters as well as thermodynamic constants to predict radionuclide migration. The identified spectroscopic properties of Am(III)-carbonate species enable monitoring time-dependent species evolution in addition to determining the thermodynamics of Am(III) in carbonate systems.